2020
DOI: 10.1177/1559325820931290
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Clinicopathological Significance of C-Reactive Protein to Albumin Ratio in Patients With Pancreatic Cancer: A Meta-Analysis

Abstract: Background: This meta-analysis explored the correlation between the C-reactive protein to albumin ratio (CAR) and survival outcomes and clinicopathological characteristics in patients with pancreatic cancer. Methods: PubMed, Embase, Web of Science, and Cochrane Library databases were comprehensively searched through October 17, 2019. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were used to evaluate the association between CAR and overall survival (OS), progression-free survival (PFS), and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Furthermore, the prognostic value of elevated CRP/Albumin ratio (CAR), reflecting increased CRP values and decreased albumin concentration as indicator of poor nutritional and activated acute phase response, has been widely explored. Elevated CAR has been shown to predict poor outcome in acute diseases including sepsis [178,179] as well as in various malignant diseases [96,99,[180][181][182][183]. Takamori et al investigated CAR for MPM patients and found a high CAR to be independently prognostic [184].…”
Section: Albumin-a Negative Acute Phase Proteinmentioning
confidence: 99%
“…Furthermore, the prognostic value of elevated CRP/Albumin ratio (CAR), reflecting increased CRP values and decreased albumin concentration as indicator of poor nutritional and activated acute phase response, has been widely explored. Elevated CAR has been shown to predict poor outcome in acute diseases including sepsis [178,179] as well as in various malignant diseases [96,99,[180][181][182][183]. Takamori et al investigated CAR for MPM patients and found a high CAR to be independently prognostic [184].…”
Section: Albumin-a Negative Acute Phase Proteinmentioning
confidence: 99%
“…In Kaplan-Meier survival curve analysis, OS and PFS were significantly better in the low-CAR group than in the high-CAR group, which also indicated that CAR could predict patient prognosis. Previous studies have shown that CAR can be used as a prognostic factor to predict the prognosis of patients with pancreatic cancer, gallbladder cancer, non-small cell lung cancer, neck squamous cell carcinoma, and cholangiocarcinoma[ 41 - 43 ]. At present, the mechanism of the effect of CAR on the prognosis of HCC patients is not completely clear, but there are some possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the prognostic value of the CRP/Alb ratio in a variety of cancer types (26,29,(32)(33)(34)(35). Yu et al showed that an elevated pretreatment CRP/Alb ratio was a prognostic marker of poor OS and CSS in patients with gastric cancer (26).…”
Section: Discussionmentioning
confidence: 99%